ECPELLA 2.0—Minimally invasive biventricular groin‐free full mechanical circulatory support with Impella 5.0/5.5 pump and ProtekDuo cannula as a bridge‐to‐bridge concept: A first‐in‐man method description. Issue 1 (14th October 2019) - Ruhparwar, Arjang; Zubarevich, Alina; Osswald, Anja; Raake, Philip W.; Kreusser, Michael M.; Grossekettler, Leonie; Karck, Matthias; Schmack, Bastian
Abstract: Background: Cardiogenic shock (CS) from biventricular heart failure that requires acute mechanical circulatory support (MCS) is associated with high mortality. Different MCS methods and techniques have emerged as a standard of care in CS. Nevertheless, the routine MCS approach carries multiple limitations such as limb ischemia, missing of left ventricular unloading and immobilization. We describe a method to establish a groin‐free full support MCS in patients with CS without the need for thoracotomy. This is the first report of the ECPELLA 2.0 concept, a peripheral groin‐free biventricular MCS in patients with acute CS. Methods and results: We discuss two patients in acute CS (INTERMACS I) treated with two peripheral MCS devices (Impella 5.0 or 5.5 surgically via an axillary artery and ProtekDuo cannula percutaneously via a right internal jugular vein) as a bridge before the implantation of a durable left ventricular assist device (LVAD). Biventricular assist device (BIVAD)‐support duration was 9 and 15 days and both of the patients were successfully bridged to a durable LVAD. As our BIVAD‐concept is groin‐free, the patients started full mobilization as early as they were weaned from the respirator 2 days after the BIVAD‐implantation. ECPELLA 2.0 provides a high cardiac output, right and left ventricular unloading with end‐organ recovery and a possibility of administration of a membrane oxygenator. There were no device‐related complications. Conclusion: The ECPELLA 2.0 biventricular support concept for patients suffering from an acute CS. Allows for rapid extubation, mobilization, and physical exercise while on full support. Additional application of a membrane oxygenator is easily feasible if required.